RISK ANALYSIS OF PD. DHARMA JAYA BEEF SUPPLY IN THE CONDITIONS OF THE COVID-19 PANDEMIC - Zulmanery Manir; Nunuk Adiarni; Afdha Yulistia (AGRIBUSINESS JOURNAL, 2021)
This research is backgrounded by the level of public consumption of beef continuing to increase which is characterized by the continued increase in public demand. DKI Jakarta is the largest consumer of beef supplied by PD. Dharma Jaya. The covid-19 pandemic that made Jakarta the epicenter of the spread of the virus had a significant impact on the company and became a threat to the availability of beef in DKI Jakarta Province. Based on these problems, this study aims to identify the risks that occur in the conditions of the Covid-19 pandemic in each business process chain. Analyze the priority level of risk handling in the conditions of the Covid-19 pandemic in each business process chain using the Pareto Diagram. Analyze risk mapping using the risk matrix chart. Provide suggestions for priority risk mitigation actions that can be carried out.The results of this study are known that the risks identified are the risk of delay in the arrival of beef cattle, the increase in the price of imported meat raw materials, damage or deterioration in the quality of meat during transportation and reception, sanitation, and hygiene are not implemented properly, handling of imported beef and distribution, equipment is not sterilized after use, there are no sanitation and disinfection efforts, no application physical distancing, there are no screening efforts on workers before slaughtering, workers are not orderly using PPE by health protocols, demand for meat has decreased, and sales targets are not achieved. The results of the risk mapping show that priority risks are in quadrants I and II.The conclusions of this study show that there are 51 risks identified, including priority risks that could occur during the Covid-19 pandemic. The actions that need to be carried out in by the quadrant map are the management and control of risks.  Risk mitigation that needs to be done in supervision and monitoring.